Gambaran Risiko Terjadinya Gangguan Female Athlete Triad Syndrome pada Mahasiswi Olahraga - Ardi Setyo Nugroho; Bambang Purwanto (Journal of Sport Science and Education, 2020)
AbstrakThe contribution of women to the progress of national sports is evidenced through the contribution of achievement in world-class competitions. Achievements achieved certainly go through a training process that is not short-lived and health problems often occur as a consequence. This study aims to describe how much the risk of the occurrence Female Athlete Triad (FAT) Syndrome in sports students. This research uses a quantitative approach with survey data collection techniques. The research respondents were 60 active students from 2014-2019 Faculty of Sports Science, Semarang State University selected by quota sampling. The Instrument research use questionnaire that refers to the Female Athlete Triad: Cumulative Risk Assessment. The results showed the risk of impaired energy availability from a history of low frequency of eating 50% (n = 30), regulate body weight 41.7% (n = 25), specific lifestyle 40% (n = 24), fasting habits 60% (n = 36) and eating disorders 65% (n = 39). The risk of menstrual disorders of menarche delayed was 25% (n = 15), oligomenorrhea 50% (n = 30) and amenorrhea secondary 53.3% (n = 32). Risk of bone disorders 30% (n = 18). The description of the results of this study shows that the risk of sports college students suffering from FAT syndrome is quite large. The most surprising finding in this study was the low level of knowledge and information related to FAT syndrome among sports students. Given the large impact on health, necessary screening and further medical examinations as well as providing education about FAT syndrome disorders to female college students.